The sharing of formative practices in school mathematics by literacy teachers - Grando, Regina Célia; Nacarato, Adair Mendes (Universidade Estadual de Campinas, 2016)
The text analyses formative practices in a group of literacy teachers, who are part of the Observatory of Education project, called “Studies and researches of school mathematics literacy practices and of teaching training”, of the São Francisco University, Itatiba, SP, for the period of 2013-2014. The project aims to investigate, through a collaborative work with basic education teachers, the school mathematical literacies practices, as well as the teachers’ formation practices of teachers who teach mathematics. We understand that the teachers’ practices when are systematized in a narrative form and shared in the researchers group and in scientific events make an academic literacy of all of the involved possible. In this way, we take as object of analysis the sharing moments of the teachers’ narratives in the researchers group and in scientific events, understating them as formative experience.